Investing in climate: A role for 'sovereign climate funds' - Kozintseva, Marianna (Institutional Knowledge at Singapore Management University, 2024)
Efforts to address climate change have generally been focused on deploying mitigation technologies. However, it is adaptation technologies (and climate risk transfer) that will have to gain an increasing share of an investment pool dedicated to climate if human systems are to stay resilient to climate forces. Just like mitigation projects, adaptation projects have a strong public goods aspect, wherein public returns exceed private returns, and thus call for the state’s involvement. We argue that sovereign climate funds (SCFs) - new types of sovereign wealth funds with a climate investment mandate - can be critical purpose-built conduits especially for undertaking the needed decades-long programs of allocating resources to adaptation projects, without hindrance from political biases or “short-termism”. They can also function as “cushions” against potential future climate funding shortfalls and dispense payouts when climate disasters strike. We discuss the various climate-related adaptation investments that SCFs would be particularly well-suited to undertake.